Vicious LQT induced by a combination of factors different from hERG inhibition - Xu, Xinping; Yin, Yue; Li, Dayan; Yao, Binwei; Zhao, Li; Wang, Haoyu; Wang, Hui; Dong, Ji; Zhang, Jing; Peng, Ruiyun (Frontiers in Pharmacology, 2022)
Since many drugs cause QT and APD prolongation or hERG inhibition are non-proarrhythmia, we aim to explore why some LQT is associated with risk while others have no risk or anti-arrhythmic effects by testing cisapride, a removed drug from the market due to causing LQT and inducing TdP. The effects of cisapride on hERG current were evaluated using whole-cell patch clamp. According to the dose-response curve of cisapride, models of its effects at different doses (10 nM, 100 nM, 1000 nM) on guinea pig heart in vitro were established. The effects of cisapride on electrocardiogram (ECG) signals and QT interval changes of guinea pigs were comprehensively evaluated by multi-channel electrical mapping and high-resolution fluorescence mapping, and the change of action potential were simultaneously detected. Cisapride dose-dependently inhibited the hERG current with a half inhibitory concentration (IC50) of 32.63 ± 3.71 nM. Completely hERG inhibition by a high dose cisapride (1000 nM) could prolong the action potential duration (APD) but no early after depolarizations (EADs) and torsades de pointes (TdP) occurred. Combining with 1 μM cisaparide and lower Mg2+/K+, APD exhibited triangulation, dispersion and instability, 2 of 12 guinea pig hearts exhibited VT. Further combined use of isoproterenol is not therapeutic and more prone to VF. HERG inhibition alone will lead to QT prolongation, along with ERP prolongation, and play an anti-arrhythmic role. However, when combined with low concentration of magnesium and potassium, the prolonged action potential will become unstable, triangular and dispersion, and it is easy to induce VT. When catecholamines combined, APD is shortened, but triangulation and dispersion still exist. At this time, VF is easily induced and can be sustained.